2015
DOI: 10.1093/ije/dyv114
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in detecting discrepancies in a clinical trial report: 260-reader evaluation

Abstract: Background: Scientific literature can contain errors. Discrepancies, defined as two or more statements or results that cannot both be true, may be a signal of problems with a trial report. In this study, we report how many discrepancies are detected by a large panel of readers examining a trial report containing a large number of discrepancies.Methods: We approached a convenience sample of 343 journal readers in seven countries, and invited them in person to participate in a study. They were asked to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Suggestions for systematic review authors on how to address internal reporting discrepancies editorial and peer-review process, as well as galley proof checking, should also be highlighted as measures for preventing objective errors. As Cole et al [15] have observed, ''Even minor discrepancies should not be neglected, as they may be the tip of an error iceberg''.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Suggestions for systematic review authors on how to address internal reporting discrepancies editorial and peer-review process, as well as galley proof checking, should also be highlighted as measures for preventing objective errors. As Cole et al [15] have observed, ''Even minor discrepancies should not be neglected, as they may be the tip of an error iceberg''.…”
Section: Resultsmentioning
confidence: 99%
“…However, some discrepancies were major, potentially reverting results in a meta-analysis or causing complete misinterpretation of results. It has also been previously emphasized that discrepancies can be a sign of deeply problematic studies, warranting further attention and verification [15]. The judgment of the relevance of discrepancies should be always collegial, involving more reviewers.…”
Section: What Should Systematic Review Authors Do In Case Of Internalmentioning
confidence: 98%
See 2 more Smart Citations
“…Little agreement exists on what constitutes effective peer review or the skills required to provide it,6 and there is little evidence that peer review does what many think it should do—ensure the quality of research 7. Although peer review is highly regarded by researchers and considered essential for publication of research8 it has many flaws: In one study, 607 peer reviewers for The BMJ detected only one third of major errors inserted into test trial reports, despite training;9 In another, 260 readers missed 95% of the 39 discrepancies in a clinical trial report 10. Peer review itself is of questionable value and could offer false reassurance.…”
mentioning
confidence: 99%